METODE TAFFLER DAN ALTMAN Z-SCORE DALAM MENGUKUR FINANCIAL DISTRESS PADA PT TIRTA MAHAKAM RESOURCES, Tbk. - Manurung, Sepbeariska; Siregar, Liper; Arshandy, Eliza; Hutagalung, Daud Immanuel (Jurnal Ilmiah Satyagraha, 2025)
Abstract – This study aims to predict the level of bankruptcy of a company using the Taffler and Altman Z-Score methods at PT Tirta Mahakam Resources, Tbk. for the period 2015-2022 and to determine the comparison of the accuracy and error rate of each method used, namely the Taffler and Altman Z-Score methods. This study uses quantitative data by taking secondary data accessed from the official website of the Indonesia Stock Exchange (www.idx.co.id). The data analysis technique used is descriptive qualitative and comparative analysis. The results of this study indicate that there are different results in predicting the level of bankruptcy produced using the Taffler method in contrast to the Altman Z-Score method. This can be seen from the highest level of accuracy is using the Altman Z-Score method with a percentage of 0% while the error rate is using the Altman Z-Score with a percentage of 100%. Thus it can be concluded that the most suitable and accurate method in predicting Financial Distress is the Altman Z-Score method.